Pearl Millet Germplasm Resources Conservation Status and Their Utilization in Crop Improvement - Vetriventhan, Mani; Kumar, Vinod; Dagunapur, Naresh Reddy; Srinivas, Raja; Jagadeesh, Kommineni; Kanchanapally, Anilkumar; Peerzada, Ovais; Elangovan, M.; Singh, Kuldeep (Springer, 2024)
Genetic resources are key to unlocking untapped potential in terms of increased productivity, improved nutrition, and enhanced climate resilience to ensure food security and nutrition. The conservation of pearl millet crop wild relatives in their natural habitats and the on-farm conservation of landraces serve as in situ strategies, while ex situ conservation, primarily through seedbanks, is the most common method. Currently, over 73,000 pearl millet accessions are conserved across 57 genebanks worldwide. Among them, the ICRISAT genebank conserves the largest collection, with 25,537 accessions originating from 52 countries. Despite the significant number of pearl millet collections held in various genebanks, taxonomical and gap analyses revealed potential gaps in the collection to enrich the pearl millet gene pool. Extensive efforts have been made to maximize the use of germplasm, resulting in the development of core and mini-core collections, and the evaluation of pearl millet genetic resources led to the identification of trait-specific sources of yield, nutrients, and biotic and abiotic stresses. By employing appropriate strategies to harness the potential of pearl millet genetic resources, novel diversity can be leveraged to breed climate-resilient and nutrient-dense cultivars that contribute to sustainable agricultural productivity and improved nutrition. This chapter provides a comprehensive overview of the conservation status of pearl millet germplasm and outlines the characterization efforts undertaken to facilitate their utilization in crop improvement and trait discovery.